(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
On 16 December 2020 the Regulation on a general regime of conditionality for the protection of the Union budget was finally approved, after having been long-awaited by scholars to test the adequacy of the response of European institutions to the rule of law crisis that is severely affecting some EU countries. From a substantive perspective, the paper aims at highlighting some elements that, albeit crucial for the functioning of the instrument, do not seem to be sufficiently defined in the final text. Moreover, since the European Council conclusions of 10 and 11 December 2020 seem to introduce some ex-post amendments to the Regulation, the paper will investigate – through a comparative analysis of the two texts – if that is the case and if the scenario can be considered as a breach of EU law by the European Council. Finally, taking into consideration the principles governing conditionality mechanisms, a preliminary assessment of the effectiveness of the Regulation as an instrument to safeguard the rule of law within the EU legal order will be developed.